Obstructive Sleep Apnoea Syndrome: Continuous Positive Airway Pressure Therapy for Prevention of Cardiovascular Risk - María Pilar Resano-Barrio; Ramón Arroyo-Espliguero; María Carmen Viana-Llamas; Olga Mediano (European Cardiology Review)
Obstructive sleep apnoea (OSA) syndrome is characterised by the presence of apnoea or obstructive hypopnoea during sleep, accompanied by hypoxia. It is estimated that the syndrome affects approximately 10% of men and 15% of women. Diagnosis and treatment rates have increased in recent years, but the condition remains undiagnosed in a high percentage of patients. Recent evidence suggests that OSA may increase the risk of cardiovascular disease. The relationship between OSA and cardiovascular disease can be explained, at least in part, by the coexistence of cardiovascular risk factors in the two pathologies, such as age, overweight, smoking and sedentary lifestyle. However, OSA has been independently associated with the risk of developing hypertension, cerebrovascular disease, ischaemic heart disease, heart failure and arrhythmias. Clinical trials that have evaluated the efficacy of continuous positive airway pressure (CPAP) treatment in primary and secondary cardiovascular prevention have not demonstrated a significant reduction in the incidence or recurrence of cardiovascular events. This article analyses the relationship between OSA and cardiovascular risk and discusses recent clinical trials on the efficacy of CPAP in primary and secondary cardiovascular prevention.